Keefektifan Model Siklus Belajar Melalui Hipotetikal Deduktif Ditinjau dari Pemahaman Konsep Kimia pada Siswa SMA - Reny, Reny; Bahar, Hasrawati; Kurnia, Andi (Indo-MathEdu Intellectuals Journal, 2025)
This descriptive Pre-Experiment research aims to determine the effectiveness of the hypothetical-deductive learning cycle model in terms of understanding the chemical concepts of SMA Negeri 5 students (subject matter of acid and base solutions). Effectiveness is reviewed from three criteria of completeness, namely individual completeness, class completeness, and indicator completeness. The research subjects were 30 students of class XI IPA 2 SMA Negeri 5. Data collection of learning outcomes was done by giving pretest and posttest. The test used was a choice question, selected as many as 25 numbers from 30 numbers after being validated for content and item validation. The data on learning outcomes obtained were analyzed using descriptive statistical techniques, namely for individual completeness of 76.279% with high effectiveness criteria. Class completeness was 50% with a fairly high effectiveness category and indicator completeness was 79.59% with a high effectiveness category. This means that chemistry learning for XI IPA SMA Negeri 5 with a hypothetical-deductive learning cycle model when viewed from students' concept understanding in solving problems regarding acid and base solutions is effective in achieving the completeness of learning outcomes.